Stability of existing Banyukuwung DAM in recent hydrology and geotechnical conditions - Juwono, Pitojo Tri; Asmaranto, Runi; Murdhianti, Ari (Civil and Environmental Science Journal (CIVENSE), 2020)
Banyukuwung Dam is located in the villages of Sukorejo and Sudo, Sumber District, Rembang Regency, Central Java Province. This dam was built in 1995-1997 to serve the needs of 7750 ha of irrigation water and 35 l/s of raw water needs. Dam type is homogeneous reservoir, has a height of 19.40 m above the riverbed and 25.40 m above the foundation excavation. The length of the dam peak is 181.00 m and the width is 5.00 m while the reservoir volume under normal water conditions is 1.64 million m3. Along with seasonal changes and extreme hydrological behavior and based on an investigation of current geotechnical conditions, stability analysis is needed based on these two conditions. It is very important to plan operational and maintenance activities related to the dam maintenance program. So that it is expected to be useful for the relevant agencies in making operational decisions. The purpose of this study was to determine the stability of the existing Banyukuwung dam based on the latest hydrological and geotechnical behavior. The results are expected to provide recommendations in the management, operation and maintenance of the dam manager.